Recurrent germline variant in RAD21 predisposes children to lymphoblastic leukemia or lymphoma - Schedel, Anne; Friedrich, Ulrike Anne; Morcos, Mina N. F.; Wagener, Rabea; Mehtonen, Juha; Watrin, Titus; Saitta, Claudia; Brozou, Triantafyllia; Michler, Pia; Walter, Carolin; Försti, Asta; Baksi, Arka; et al. (International journal of molecular sciences, 2022)
Somatic loss of function mutations in cohesin genes are frequently associated with various cancer types, while cohesin disruption in the germline causes cohesinopathies such as Cornelia-de-Lange syndrome (CdLS). Here, we present the discovery of a recurrent heterozygous RAD21 germline aberration at amino acid position 298 (p.P298S/A) identified in three children with lymphoblastic leukemia or lymphoma in a total dataset of 482 pediatric cancer patients. While RAD21 p.P298S/A did not disrupt the formation of the cohesin complex, it altered RAD21 gene expression, DNA damage response and primary patient fibroblasts showed increased G2/M arrest after irradiation and Mitomycin-C treatment. Subsequent single-cell RNA-sequencing analysis of healthy human bone marrow confirmed the upregulation of distinct cohesin gene patterns during hematopoiesis, highlighting the importance of RAD21 expression within proliferating B- and T-cells. Our clinical and functional data therefore suggest that RAD21 germline variants can predispose to childhood lymphoblastic leukemia or lymphoma without displaying a CdLS phenotype.
This article belongs to the Special Issue Genetics and Epigenetics in Complex Diseases
Gesehen am 27.06.2022